SEEDING HEALTH PROJECT 1ST EDITION: INTEGRATION BETWEEN THE COMMUNITY AND FUTURE DOCTORS (CIPEEX, 2026)
Introduction: The current academic environment highlights not only the importance of technical training in educational centers but also the need to transmit this knowledge to the community, promoting reflection and behavioral changes. In this context, outreach projects become fundamental to integrating teaching and social practice. Objective: To report the experience of implementing the outreach project "Sowing Health – 1st Edition," developed by first-year students of the 27th class of the Medical School at the Evangelical University of Goiás. Method: Eighteen recreational workshops were organized for children and adults in the community. To assess the impact of the activities, participating students completed a questionnaire reflecting on the project's impact on their education. Results: Analysis of the responses revealed that the students recognized the project as an essential tool for developing medical knowledge, as well as communication and leadership skills. The positive impact of community outreach on the consolidation of academic practice was also highlighted. Conclusion: The workshops demonstrated relevance not only in strengthening technical knowledge but also in cultivating human, supportive, and empathetic values. Thus, the extension project proved essential for the comprehensive training of future doctors, combining academic learning and social commitment.
Keywords: Community extension; Students, Medical; health promotion